Pelatihan Kompilasi Laporan Keuangan Di Kalangan Siswa SMA/SMK Berbasis Online - Mulyani Rizki (Universitas 17 Agustus 1945 Semarang, 2023)
This Community Service Activity (PKM) is one manifestation of the Tri Dharma of Higher Education, namely providing benefits to the community. This PKM activity is aimed at high school students located on Jalan Social Palembang. The method for implementing community service activities is by providing online training. The target participants for this training are Karya Ibu High School students. For the Raden Fatah State Islamic University, the Faculty of Economics and Islamic Business is one of the means to introduce the Raden Fatah State Islamic University of Palembang and is a community service activity carried out by Lecturers at the Raden Fatah State Islamic University of Palembang to be able to apply the knowledge they have to the community. . The topic chosen for this activity was training in making financial reports among high school/vocational school students. This topic was chosen because it remembers the importance of understanding in preparing financial reports to be able to measure the company's performance and financial position. The output resulting from this community service activity is a module in the form of a financial report compilation and as the final stage, we will create a report on the implementation of this Community Service (PKM) task.